PROTECTION OF CULTURAL GOODS IN CROATIA AND SERBIA WITH AN EMPHASIS ON RESTRICTIONS OF OWNERSHIP: / - Klasiček, Dubravka; Nedić, Tomislav; Budiša, Vlasta (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2023)
In the Art. 52 of the Constitution of Croatia, cultural goods are declared as goods of special interest to the Republic of Croatia that enjoy the special protection of the state. Art. 69 of the Constitution stipulates that the state protects, among other things, cultural goods as spiritual national values. The Constitution of Serbia, in its art. 89, determines the obligation of every person to preserve, among other things, cultural heritage as an asset of general interest. The authors believe that something similar exists in most modern legal systems. Various legal subjects own many cultural goods. Still, given their status and the special protection they enjoy, the owners of such goods are subject to certain ownership restrictions and have obligations that owners of most other things do not have.In this paper, the authors will analyze Croatian and Serbian legal acts that regulate the protection of cultural goods with special emphasis on restrictions of ownership over cultural goods in these two countries. There are certain similarities, but also some differences between how the protection of cultural goods is regulated in Croatia and Serbia. The types of cultural goods and their protection vary in certain ways, as well as the rights and obligations of owners of cultural goods.
Keywords: cultural good; restriction of ownership; protection of cultural goods; owner's rights; property; owner's obligations